تصميم موقع ويب لالدارة من وكالة بيع السيارات - كير, عماد الدين; عبد الحكيم ,بريم; أسامة, خلف (Université of Eloued جامعة الوادي, 2026)
"In the digital era we live in today, e-commerce has become an inseparable part of our daily lives, as many individuals seek to complete their commercial transactions online due to easy access, convenience, and time savings. This project aims to establish a specialized website for car sales, providing customers with an innovative and secure shopping experience through this platform. ""في العصر الرقمي الذي نعيشه اليوم، أصبحت التجارة اإللكترونية جز ًءا ال يتجزأ من حياتنا اليومية، حيث يسعى العديد من األشخاص إلتمام معامالتهم التجارية عبر اإلنترنت بسبب سهولة الوصول، الراحة، وتوفير الوقت, يهدف هذا المشروع إلى إنشاء موقع إلكتروني متخصص في بيع السيارات، بحيث يوفر تجربة تسوق مبتكرة وآمنة للعمالء من خالل هذا الموقع "
مذكرة تخرج سنة ثالثة ليسانس إعلام آلي
Keywords: Horse Power; Four-wheel; Car Purchase; Payment Gateway; القوة الحصانية; نظام الدفع الرباعي; بوابة الدفع; شراء سيارات